Derivation of the Early Carboniferous Wedgeport pluton by crystal fractionation of a mafic parental magma: a rare case of an A-type granite within the Meguma terrane (Nova Scotia, Canada). (13th August 2019) - Shellnutt, J. Gregory; Dostal, Jaroslav
Abstract: The Cambrian–Ordovician metasedimentary rocks of the Meguma terrane (Canadian Appalachians) were extensively intruded by silicic plutons during Middle Devonian to Early Carboniferous times. Syn-plutonic but volumetrically minor mafic-ultramafic intrusions were also emplaced. In most localities, the silicic plutons and mafic-ultramafic intrusions do not appear to be petrogenetically related and are likely derived from different sources. The Attwoods Brook gabbronorite of SW Nova Scotia yielded an in situ zircon weighted-mean 206 Pb– 238 U age of 357.9 ± 3.3 Ma that is within the uncertainty of the age of the neighbouring Wedgeport pluton (357 ± 1 Ma). The Wedgeport pluton is a rare example of a mantle-derived, peraluminous A-type granite within the Meguma terrane. The similar ages and Nd isotopes of the Attwoods Brook gabbronorite (εNd ( t ) = +1.1 to +4.0) and Wedgeport pluton (εNd ( t ) = +2.1 to +3.3) suggest the two intrusions are petrogenetically related. Fractional crystallization modelling demonstrates that a parental magma similar to the Attwoods Brook gabbronorite can produce residual silicic liquids that resemble the granites of the Wedgeport pluton, indicating that they could be members of the same intrusive complex. The emplacement of the gabbronorite and Wedgeport pluton occurred during a period of tensional plate stress that was contemporaneous with rifting of the Maritimes Basin that produced the Fountain Lake continental flood basalts and A-type granites of the Cobequid Highlands within the Avalon terrane. It is possible that the Early Carboniferous rocks of SW Nova Scotia are related to the rifted-related magmatism within the Maritimes Basin.